neurogenin2 elicits the genesis of retinal neurons from cultures of nonneural cells - Yan, Run-Tao (The National Academy of Sciences, 2001)
neurogenin2 (ngn2) encodes a basic helix–loop–helix transcription factor and plays an important role in neurogenesis from migratory neural crest cells. Its role in retinal development is poorly understood. We observed that in the developing chick retina, ngn2 was expressed in a subpopulation of proliferating progenitor cells. Ectopic expression of ngn2 in nonneural, retinal pigment epithelial cell culture triggered de novo generation of cells that expressed neural-specific markers and exhibited neuronal morphologies. Further molecular and morphological analyses showed that the main products of the induced neurogenesis were cells resembling young photoreceptor cells and cells resembling retinal ganglion cells. The generation of multiple cell types suggests that ngn2 induces various retinal pathways. Thus, unlike in the peripheral nervous system where ngn2 specifies one type of sensory neuron, ngn2 in the retina is likely involved in a common step leading to different cellular pathways. Our finding that ngn2 can instruct nonneural retinal pigment epithelial cells to differentiate toward retinal neurons demonstrates one possible way to induce de novo retinal neurogenesis.